Reconceptualizing Urbanism: Insights From Maya Cosmology - Lucero, Lisa J.; Gonzalez Cruz, Jesann (Frontiers in Sustainable Cities, 2020)
Sustainable practices in the present are typically designed to mitigate immediate concerns over decadal timespans. In the face of exponential population growth, overuse of resources, and global climate change, this time span is inadequate; longer, more resilient and sustainable options need to be implemented. Here, we tackle the intersection of human behavior and the urban environment by taking a holistic approach—that is, a non-anthropocentric approach critical to ensure the longevity, or even survival, of the planet. We thus approach urbanism as we would any ecosystem, with the broad understanding that the urban, the rural, humans, and non-humans are all interdependent. One cannot understand cities without an understanding of the surrounding rural or non-center areas, thus making critical an appreciation of urban-rural interdependence (URI). The holistic model is based on insights from the ancient Maya of Central America—a tropical society where farmers practiced widespread, sustainable agriculture for 4000 years without denuding the landscape. The Classic Maya accomplished this feat in large part due to their sustainable URI and cosmocentric worldview (CWV)—that is, a cosmology of conservation, or merged existence, where people, animals, plants, rivers, stones, clouds, etc. each played a role in maintaining the world. Their CWV was also expressed in urban planning through manifestations of traditional knowledge, multi-purpose designs, and local resource networks. Insights from the Maya indicate that diversity is fundamental—across all scales; diverse strategies are flexible, spread risk, and are resilient in the face of change. As such, we present past lessons from Maya kings and farmers who built cities with reservoirs, causeways, monumental constructions and other urban features that integrated the built into the existing environment, ultimately resulting in green cities interspersed with farmsteads and managed biodiverse forests. In brief, our holistic model suggests possibilities for the re-integration of nature and culture, with the goal of a resilient URI.